Preparation method of flame-retardant composite aerogel with function of photocatalytically degrading dye

By combining chitosan, carboxychitosan with TiO2@MXene complex, a stable three-dimensional network structure is formed using 1-ethyl-3-methylimidazole acetate ionic liquid and ultrasonic/microwave technology, which solves the problems of insufficient strength of the existing aerogel structure and limited photocatalytic activity, and achieves efficient flame retardant and photocatalytic degradation effects.

CN119875195AActive Publication Date: 2025-04-25ANHUI AGRICULTURAL UNIVERSITY

Patent Information

Application Number
CN202510361567.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The structural strength of the existing chitosan/TiO2 composite aerogel is insufficient, the dye degradation rate decreases after repeated use, and the photocatalytic activity of TiO2 is limited, resulting in low photocatalytic degradation efficiency.

Method used

By combining chitosan, carboxychitosan with TiO2@MXene complex, 1-ethyl-3-methylimidazole acetate ionic liquid is used as solvent and reaction medium, and ultrasonic and microwave radiation are used to promote electrostatic self-assembly and cross-linking reactions to form a stable three-dimensional network structure.

Benefits of technology

It significantly improves the structural stability, flame retardant properties and photocatalytic activity of composite aerogels, extends the service life, and achieves efficient dye degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875195A_ABST
    Figure CN119875195A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of composite aerogel functional materials, and discloses a preparation method of flame-retardant composite aerogel with a function of photocatalytically degrading dye, which comprises the following steps: dissolving chitosan in 1-ethyl-3-methylimidazole acetate ([EMIM] [Ac]) acidic ionic liquid, adding a TiO2-coated MXene compound under the action of ultrasonic waves to perform electrostatic self-assembly, and performing ultrasonic treatment to obtain the flame-retardant composite aerogel with the function of photocatalytically degrading dye. Then adding low-molecular carboxyl chitosan and a small-molecular cross-linking agent under microwave radiation to enhance a cross-linking reaction and an electrostatic force effect, and then performing microwave vacuum freeze drying to prepare the chitosan / carboxyl chitosan / TiO2 (at) MXene composite aerogel material. The method is simple and easy to implement, and the obtained composite aerogel has the advantages of being high in structural stability, low in dissolution loss rate, high in porosity, efficient in flame retardance, good in photocatalytic activity and the like, and has wide application prospects in the fields of photocatalytic degradation of pollutants, high-temperature heat insulation, flame retardance, fire prevention and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of a composite aerogel having both flame retardancy and photocatalytic degradation of dyes, and in particular to a preparation method of a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel and application of the aerogel in flame retardancy and fireproofing and photocatalytic degradation of dyes, belonging to the field of composite aerogel functional materials. Background Art

[0002] Aerogels are widely used in the fields of fire resistance and thermal insulation due to their high porosity, low thermal conductivity, ultra-light structure and high thermal insulation performance [Chen J, Xie H, Lai X, et al. An ultrasensitive fire-warning chitosan / montmorillonite / carbon nanotube composite aerogel with high fire-resistance[J]. Chemical Engineering Journal, 2020, 399: 125729]. In recent years, biomaterial-derived flame-retardant aerogels have attracted much attention due to their advantages such as renewability, environmental friendliness, low economic cost, light weight and high thermal insulation performance. Natural polysaccharide polymers are one of the most abundant renewable biomass materials with better biodegradability and environmental friendliness than fossil-based materials, making them an excellent candidate for the production of sustainable aerogels in the field of flame retardant materials. Therefore, people are committed to the development of polysaccharide-based aerogel products due to their high porosity, low density, non-toxicity, biosustainability and biodegradability. Chitosan is a biopolymer with amino polysaccharides and is considered a promising alternative to traditional flame retardants because it contains abundant hydroxyl and amino groups, which give chitosan aerogel excellent carbonization and thermal insulation capabilities [ChenH Q, Xu YJ, Jiang ZM, et al. The thermal degradation property and flame-retardant mechanism of coated knitted cotton fabric with chitosan and APP byLBL assembly[J]. Journal of Thermal Analysis and Calorimetry, 2020, 140: 591-602]. Although chitosan has many advantages and applications, its flame retardant properties are limited. Many studies have shown that the addition of materials such as montmorillonite, carbon nanotubes, and graphene oxide can significantly improve the flame retardant properties of organic aerogels. However, inorganic substances such as montmorillonite and graphene oxide may have poor compatibility with the chitosan aerogel matrix, resulting in the destruction of the aerogel network structure and seriously affecting the mechanical properties of the aerogel.

[0003] MXene is an emerging two-dimensional layered transition metal carbide / carbonitride, where M represents an early transition metal and X represents carbon and / or nitrogen. Due to its outstanding physical and chemical properties, MXene has shown potential applications in many fields, including catalysis, batteries, thermal energy storage, and electromagnetic interference. MXene has also been explored as a flame retardant due to its excellent thermal stability, high specific surface area, good catalytic activity, excellent mechanical properties, and tunable chemical properties [Yu B, Yuen ACY, XuX, et al. Engineering MXene surface with POSS for reducing fire hazards ofpolystyrene with enhanced thermal stability[J]. Journal of Hazardous Materials, 2021, 401: 123342], and its advantages are also conducive to the development of high-performance polymer composites. Recent studies have demonstrated the catalytic effect of titanium-containing metal compounds in MXene, which can effectively inhibit the release of smoke and promote the formation of a carbon layer [Liu C, Wu W, Shi Y, et al. Creating MXene / reduced graphene oxide hybridtowards highly fire safe thermoplastic polyurethane nanocomposites[J].Composites Part B: Engineering, 2020, 203: 108486]. The incorporation of MXene nanosheets can significantly improve the thermal insulation and flame retardant properties of aerogels. At the same time, the groups on the surface of MXene can form a stable hydrogen bond structure with the aerogel matrix. The introduction of MXene into chitosan aerogel can enhance the mechanical strength of the matrix and improve the flame retardant properties of the aerogel. At the same time, the traditional method to improve the flame retardant properties of chitosan aerogel is to phosphorylate chitosan, but the molecular weight of chitosan in strong acid is significantly reduced, so the phosphorylation reaction is difficult to control and there is smoke and toxicity in the combustion process. MXene can form a strong hydrogen bond with chitosan, which can improve the mechanical strength of chitosan composite aerogel without destroying the performance of chitosan and also have good flame retardant properties. MXene can be well mixed with chitosan aerogel to form a MXene / chitosan complex, thereby improving the flame retardant properties of chitosan aerogel.

[0004] The treatment and recycling of printing and dyeing wastewater has become an urgent problem to be solved in society. Titanium dioxide (TiO2) is a new type of photocatalytic material that can convert organic pollutants such as dyes, surfactants, polymers, aromatic hydrocarbons, etc. in printing and dyeing wastewater into small molecular non-toxic compounds under ultraviolet light. Most of the energy in the reaction process comes from solar radiation, and there is no secondary pollution in the photocatalytic reaction process. The photocatalytic efficiency of TiO2 is mainly limited by its large band gap and the rapid recombination of photogenerated electron / hole pairs. The powdered TiO2 photocatalyst has low adsorption capacity and is easy to agglomerate. Photogenerated electrons and holes are easy to recombine, and the utilization rate of visible light is low. It is difficult to separate from the solution, which is not conducive to recycling and is not suitable for large-scale use in industry. At present, chitosan / TiO2 composite aerogel can efficiently treat wastewater and is easy to recycle and reuse. The rich amino and hydroxyl groups in chitosan can effectively enrich pollutants in water. The three-dimensional network formed by chitosan can evenly load TiO2, which is conducive to the adsorption and photocatalytic degradation of pollutants. However, the existing chitosan / TiO2 composite aerogel has insufficient structural strength, and the dye degradation rate decreases significantly after repeated use for a certain number of times. In addition, the separation efficiency of the photogenerated electrons and holes of TiO2 in the aerogel is limited, resulting in low photocatalytic activity and dye degradation rate, and a long time to degrade the dye. Summary of the invention

[0005] In view of the above-mentioned problems existing in the prior art, the object of the present invention is to provide a method for preparing and applying a composite aerogel having both flame retardancy and photocatalytic degradation of dyes. By compounding chitosan / carboxyl chitosan / TiO2@MXene, a composite aerogel material with strong structural stability, low dissolution rate, high porosity, high flame retardancy and good photocatalytic activity is obtained. The composite aerogel material has broad application prospects in the fields of photodegradation of pollutants in wastewater, high-temperature insulation, flame retardancy and fire prevention.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A flame-retardant composite aerogel with photocatalytic degradation of dyes is disclosed. The chitosan is dissolved in 1-ethyl-3-methylimidazolium acetate ([EMIM][Ac]) ionic liquid, a TiO2@MXene complex is added under ultrasonic action for electrostatic self-assembly, low-molecular carboxyl chitosan and a small molecule cross-linking agent are added under microwave radiation to enhance the cross-linking reaction and electrostatic force, and then the aerogel is obtained by microwave vacuum freeze-drying.

[0007] Preferably, the C6 carboxyl content of the low molecular weight carboxyl chitosan is 50.64-71.26%, the degree of deacetylation is 89.17-96.48%, the viscosity average molecular weight is 0.35-0.89 thousand, the solubility in water is 17.83-28.02 g / 100 mL, the isoelectric point pH=4.7-5.1, and its structural formula is as follows:

[0008] The flame retardant composite aerogel with photocatalytic degradation of dye has a dissolution rate of 7.06-14.51% and a specific surface area of ​​13.72-32.96 m 2 / g, the average pore size is 60.3-96.9μm, the porosity is 81.42-90.68%, the limiting oxygen index is 30.5-40.1%, the photodegradation rate of methylene blue (MB) dye is 80.79-100% after 2h, and the photodegradation rate of rhodamine B (RhB) dye is 82.65-98.26%.

[0009] The method for preparing the flame-retardant composite aerogel capable of photocatalytically degrading dyes of the present invention is carried out according to the following steps: (1) 1-2 g of LiF was dissolved in 20-40 mL of 9 mol / L HCl solution, and stirred at room temperature for 30-60 min to obtain a mixed solution. Then 1-2 g of Ti3AlC2 powder was slowly added to the LiF / HCl mixed solution, and slowly stirred (speed 40-100 rpm) at 45 °C for 48-60 h. The solid was collected by filtration and washed with deionized water for 3-5 times, and then centrifuged at 3500-5000 rpm for 10-20 min until the pH of the solid was 6.0-6.4. The solid was treated with a high-power ultrasonic machine at 500-680 W for 60-80 min, and then centrifuged at high speed (speed 8200-12000 rpm) for 6-10 min to obtain uniformly dispersed MXene nanosheets.

[0010] (2) Ultrasonic dispersion of anatase TiO2 sol with a mass concentration of 0.1-0.2% for 20-30 minutes, then adding the MXene nanosheets and stirring and dispersing for 10-20 minutes, then adding 10 mL of anhydrous ethanol and ultrasonically treating for 1-2 hours, transferring the mixed solution to a reactor and performing a hydrothermal reaction at 100-120° C. for 3-5 hours, cooling to room temperature, centrifuging and separating the product, washing with an ethanol solution with a mass concentration of 60%, and then freeze-drying to obtain a TiO2@MXene composite; the mass ratio of anatase TiO2 to MXene nanosheets is 1-6:1.

[0011] (3) Dissolving chitosan in 1-ethyl-3-methylimidazolium acetate ionic liquid at 60-80° C. to prepare a solution with a mass concentration of 1-4%, adding TiO2@MXene composite to carry out ultrasonic chemical reaction at 50-70° C. for 1-3 h, standing for 20-40 min, and then adding low molecular weight carboxyl chitosan and small molecule crosslinking agent to carry out crosslinking reaction under microwave radiation for 45-140 min, so that chitosan, low molecular weight carboxyl chitosan and TiO2@MXene composite form multi-site chemical crosslinking and electrostatic force; the mass ratio of chitosan to TiO2@MXene composite is 1:1; the mass ratio of chitosan to low molecular weight carboxyl chitosan is 3-10:1; the mass ratio of chitosan to small molecule crosslinking agent is 4-10:1; the small molecule crosslinking agent is selected from tartaric acid, malic acid, oxalic acid, glutamic acid, maleic acid or maleic anhydride.

[0012] (4) After the reaction is completed, the composite hydrogel is allowed to stand for 20 to 45 minutes, and is treated with an ultrasonic defoamer for 30 to 90 minutes to remove bubbles inside the composite hydrogel. The composite hydrogel is then placed in an ultra-low temperature refrigerator at -80 to -65°C for pre-freezing for 6 to 10 hours, and then subjected to microwave vacuum freeze drying for 18 to 24 hours to obtain a composite aerogel that is flame retardant and has photocatalytic properties for degrading dyes (i.e., chitosan / carboxyl chitosan / TiO2@MXene composite aerogel).

[0013] Preferably, in step (3), the 1-ethyl-3-methylimidazolium acetate ionic liquid is acidic, and its pH is 4.2 to 5.0.

[0014] Preferably, in step (3), the power of the ultrasonic wave in the ultrasonic chemical reaction is 240-360W.

[0015] Preferably, in step (3), the power of microwave radiation is 620-800 W, and the temperature of microwave radiation is 50-65° C.

[0016] Preferably, in step (4), the power of the ultrasonic defoamer is 1400-2100W.

[0017] Preferably, in step (4), the temperature of microwave vacuum freeze drying is -86 to -70°C, the microwave power is 1800 to 2400 W, and the vacuum degree is 6 to 15 Pa.

[0018] By optimizing the mass ratio of chitosan to low molecular weight carboxyl chitosan and TiO2@MXene composite, ultrasonic reaction time, microwave radiation reaction temperature and time, the amount of small molecule cross-linking agent, and microwave vacuum freeze-drying conditions, a series of composite aerogel materials with different porosities can be obtained.

[0019] The chitosan / carboxyl chitosan / TiO2@MXene composite aerogel of the present invention can be used for flame retardancy and fire prevention and photocatalytic degradation of dyes in wastewater, and the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel after photodegradation of the dye can be regenerated by decomposing the dye under ultraviolet irradiation in clean water and can be reused.

[0020] Compared with the prior art, the preparation principle and beneficial effects of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel in the present invention are embodied in: 1. The present invention uses 1-ethyl-3-methylimidazolium acetate ionic liquid as a solvent and reaction medium, which has high hydrogen bond alkalinity, low viscosity, low vapor pressure, non-volatility, can be recycled, and is green and environmentally friendly; 1-ethyl-3-methylimidazolium acetate is an environmentally friendly imidazole acidic ionic liquid miscible with water, which is easier to dissolve chitosan, and makes the amino group of chitosan carry a positive charge, thereby increasing the hydrogen bond and electrostatic force between the amino group and the negatively charged groups such as -OH, -F, and -O on the surface of the TiO2@MXene composite, thereby forming an aerogel structure with strong stability; at the same time, the 1-ethyl-3-methylimidazolium acetate ionic liquid can absorb water generated by the reaction of chitosan with low molecular weight carboxyl chitosan and a small molecule cross-linking agent, thereby promoting the forward cross-linking reaction and further enhancing the three-dimensional skeleton structure of the composite aerogel.

[0021] 2. The low molecular weight carboxyl chitosan used in the present invention (its C6 carboxyl content is 50.64-71.26%, the deacetylation degree is 89.17-96.48%, the viscosity-average molecular weight is 0.35-0.89 thousand, the solubility in water is 17.83-28.02 g / 100 mL, and the isoelectric point pH=4.7-5.1) has good water solubility compared with ordinary chitosan, and can avoid the use of acid and organic solvents and environmental pollution. In addition, the carboxyl chitosan molecule contains both carboxyl and amino groups, and is an amphoteric polyelectrolyte, which is similar to the protein structure, and has better biocompatibility and human affinity. The carboxyl group at the C6 position in the low molecular weight carboxyl chitosan molecule can undergo amide bond cross-linking with the amino group of chitosan, and the amino and hydroxyl groups in the molecule can form multi-site hydrogen bonds with the abundant -OH, -F, -O and other groups on the surface of the TiO2@MXene complex. At the same time, the low molecular weight carboxyl chitosan has a small molecular weight (viscosity-average molecular weight of 0.35 to 0.89 thousand) and low solution viscosity, and is easy to mix evenly with the macromolecular chitosan, which promotes the formation of multi-site cross-linking between low molecular weight carboxyl chitosan macromolecules, and significantly increases the skeleton strength and structural stability of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel matrix.

[0022] 3. The present invention utilizes a small molecule cross-linking agent to undergo a cross-linking reaction with chitosan, carboxyl chitosan and TiO2@MXene in 1-ethyl-3-methylimidazole acetate ionic liquid. The carboxyl group and acid anhydride in the small molecule cross-linking agent can respectively cross-link with the amino group and hydroxyl group of chitosan and carboxyl chitosan to form a covalent bond, and produce hydrogen bonds and electrostatic forces with -OH, -F, -O and other groups in the TiO2@MXene composite, and further electrostatically self-assemble to form a composite aerogel with a three-dimensional skeleton structure. No surfactant or emulsifier needs to be added, and the process has the advantages of simple and controllable process, and the three-dimensional network structure of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel can be enhanced, and the dissolution loss rate is small, the mechanical properties are high, and the flame retardant and photocatalytic properties are good.

[0023] 4. The present invention dissolves chitosan in 1-ethyl-3-methylimidazolium acetate ionic liquid, adds TiO2@MXene complex to carry out ultrasonic chemical reaction, and promotes the dispersion of chitosan macromolecular chain and the hydrogen bonding of chitosan and TiO2@MXene through the multiple effects of ultrasonic dispersion, crushing, activation, etc. At the same time, ultrasonic wave produces cavitation effect, and the formation, growth and collapse of cavitation bubbles will occur in the reaction liquid. When the cavitation bubbles collapse, high temperature and high pressure are generated in a very short time and in a very small space of the cavitation bubbles, which provides an energy source for ultrasonic chemical synthesis and greatly accelerates the electrostatic assembly of chitosan and TiO2@MXene complex. Ultrasonic wave has a significant dispersing effect on chitosan macromolecules, and the entangled chitosan macromolecular chains are evenly separated through the strong impact and cavitation of ultrasonic wave, so that chitosan and TiO2@MXene complex sheets are fully in contact, and the positively charged amino groups in chitosan are promoted to hydrogen bond with -OH, -F, -O and other groups on the surface of TiO2@MXene, thereby forming a three-dimensional mesh structure with stable skeleton.

[0024] 5. The present invention adopts microwave radiation to catalyze the cross-linking reaction between chitosan and TiO2@MXene, low molecular carboxyl chitosan and small molecule cross-linking agent. Microwave has the advantages of fast heating, precise temperature control and energy saving. In the microwave radiation reaction, microwave radiation can be used to effectively act on polar substances to accelerate the reaction. The radiation effect of microwaves can increase the kinetic energy of chitosan and TiO2@MXene, low molecular carboxyl chitosan and small molecule cross-linking agent, promote the movement between molecular chain segments, accelerate the multi-site cross-linking reaction rate of chitosan and TiO2@MXene complex, low molecular carboxyl chitosan and small molecule cross-linking agent, save reaction time and reduce energy consumption, and enhance the aerogel skeleton structure.

[0025] 6. After the composite hydrogel is left to stand for aging, the present invention uses an ultrasonic defoamer to remove bubbles inside the composite hydrogel. The ultrasonic defoamer mainly uses ultrasound to produce cavitation in the liquid, so that the gas dissolved in the liquid continuously condenses into very fine bubbles, and finally becomes spherical bubbles and detaches from the liquid surface, thereby achieving the purpose of liquid degassing and defoaming. After being treated with an ultrasonic defoamer, the components in the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel can be more closely combined, which is beneficial to increase the skeleton stability and mechanical properties of the composite aerogel.

[0026] 7. The present invention pre-freezes the chitosan / carboxyl chitosan / TiO2@MXene composite hydrogel in an ultra-low temperature refrigerator, and then freeze-dries it by microwave vacuum to obtain a composite aerogel. Pre-freezing slows down the freezing speed of water inside the chitosan / carboxyl chitosan / TiO2@MXene composite hydrogel, thereby reducing the risk of water crystallization during the freezing process, which helps to form a stable three-dimensional skeleton structure. Pre-freezing can also reduce crystallization and deformation during freeze-drying of the composite aerogel, effectively avoiding the structural collapse of the composite aerogel caused by the rapid removal of water, and significantly improving the skeleton strength of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel. The present invention uses microwave vacuum freeze drying to obtain chitosan / carboxyl chitosan / TiO2@MXene composite aerogel, combines microwave drying and vacuum drying, can give full play to their respective advantages, sublimation drying of ice crystals generated inside chitosan / carboxyl chitosan / TiO2@MXene hydrogel during pre-freezing under vacuum and below the eutectic temperature, and provides sublimation latent heat to the material to be dried in a frozen state through a microwave generator, and quickly removes moisture from the composite aerogel. Compared with the disadvantage of slow conventional heat conduction rate under vacuum, the drying time is shortened, the drying efficiency is improved, the microwave vacuum freeze drying temperature is uniform, the water molecules in the composite aerogel are evenly distributed, the moisture drying rate is consistent, the network porous structure of the composite aerogel is maintained, and the stability of the composite aerogel skeleton structure is enhanced.

[0027] 8. The present invention synthesizes TiO2@MXene composite materials through hydrothermal reaction. Since the Fermi level of MXene nanosheets is lower than that of TiO2, electrons are induced by light to transfer from the (conduction band) CB of TiO2 to the metal MXene, and holes are left in the valence band (VB) of TiO2. A Schottky barrier is generated at the interface, which prevents the diffusion of electrons to TiO2 and effectively inhibits the recombination of electrons and holes on the surface of TiO2, thereby improving the photocatalytic activity of the TiO2@MXene composite; at the same time, it avoids the defects of TiO2 such as large band gap, easy recombination of carriers, easy agglomeration of particles, and limited photocatalytic performance. Adding the TiO2@MXene composite to the chitosan / carboxyl chitosan matrix to construct a stable composite aerogel can effectively improve the removal rate of dye pollutants, and at the same time, it has high photocatalytic activity, fast dye degradation rate, good recycling, and great potential for practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 and Figure 2 This is a schematic diagram of the preparation principle of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel of the present invention.

[0029] Figure 3 This is a scanning electron microscope image of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel in test item 2 of the present invention. DETAILED DESCRIPTION

[0030] In order to have a better understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to the following embodiments.

[0031] The test method for the photocatalytic degradation of dye performance of the aerogel obtained in the following example is as follows: the initial concentration of methylene blue (MB) dye is 10 mg / L, and a certain amount of composite aerogel (TiO2 mass concentration is 0.005%) is taken. Mix the samples in the dark, set the stirring speed to 300 rpm and start timing. At this time, the sample time is recorded as "-60 min". Use a pipette to transfer 3 ml to a centrifuge tube. Use a disposable syringe with a Nylon syringe filter to filter insoluble substances such as composite aerogels and transfer them to a cuvette. Use deionized water as a reference sample for measurement. Perform absorbance tests on samples in the wavelength range of 400 to 800 nm. After the test, wash the cuvette three times with dilute hydrochloric acid, then wash with anhydrous ethanol, and finally dry it with a hair dryer. Take samples every 20 min for absorbance testing. When sampling is performed for the fourth time, the time is recorded as 0 min. At the same time, turn on the LED ultraviolet lamp, perform the same operation at a wavelength of 365 nm and a power of 75 W, and stop using the ultraviolet LED lamp 20 min, 40 min, 60 min, 80 min, 100 min, and 120 min after the start of recording. When photocatalytic degradation of Rhodamine B (RhB) dye is performed, the Nylon filter is replaced with a glass fiber filter, and the other steps remain unchanged. The absorbance at the highest point of the characteristic peak of the absorbance curve is converted to the corresponding dye concentration through the standard curve. The initial dye concentration is expressed as C0 mg / L, and the dye concentration at a certain moment is expressed as C t The photodegradation rate of the dye in the dye solution is expressed as mg / L as follows: .

[0032] 1. Preparation of chitosan / carboxyl chitosan / TiO2@MXene composite aerogel Example 1 (1) Dissolve 1 g of LiF in 25 mL of 9 mol / L HCl solution and stir at room temperature for 40 min to obtain a mixed solution. Then slowly add 1 g of Ti3AlC2 powder to the LiF / HCl mixed solution and slowly stir (45 rpm) at 45 °C for 48 h. Collect the solid by filtration and wash it with deionized water three times. Then centrifuge it at 3800 rpm for 12 min until the pH value of the solid is 6.0. Treat it with a 540 W high-power ultrasonic machine for 65 min. Then centrifuge it at high speed (8500 rpm) for 6 min to obtain uniformly dispersed MXene nanosheets.

[0033] (2) Anatase TiO2 sol with a mass concentration of 0.18% was ultrasonically dispersed for 25 min, and MXene nanosheets (the mass ratio of anatase TiO2 to MXene was 1:1) were added and stirred for 15 min. Then, 10 mL of anhydrous ethanol was added and ultrasonically treated for 1 h. The mixed solution was transferred to a reactor and subjected to a hydrothermal reaction at 100 °C for 3 h. After cooling to room temperature, the product was centrifuged and separated, washed with 60% ethanol solution, and then freeze-dried to obtain the TiO2@MXene composite.

[0034] (3) Chitosan was dissolved in 1-ethyl-3-methylimidazolium acetate ionic liquid at pH 4.8 at 70°C to prepare a solution with a mass concentration of 1.5%, and TiO2@MXene composite (the mass ratio of chitosan to TiO2@MXene composite was 1:1) was added to the solution. Ultrasonic (ultrasonic power was 260 W) chemical reaction was carried out at 50°C for 1.5 h, and the mixture was allowed to stand for 25 min. Then, low molecular weight carboxyl chitosan (low molecular weight carboxyl chitosan) was added at a mass ratio of chitosan to low molecular weight carboxyl chitosan of 4:1. The C6 carboxyl content is 53.85%, the deacetylation degree is 90.22%, the viscosity-average molecular weight is 7,200, the solubility in water is 20.70 g / 100 mL, and the isoelectric point pH is 5.0) and the small molecule cross-linking agent malic acid (the mass ratio of chitosan to malic acid is 4:1) are cross-linked under microwave radiation (the power of microwave radiation is 640 W, and the microwave radiation temperature is 50°C) for 60 minutes to form multi-site chemical cross-linking and electrostatic force between chitosan, low molecular carboxyl chitosan and TiO2@MXene composite.

[0035] (4) After the reaction, the composite hydrogel was aged for 25 min, treated with an ultrasonic defoamer (the power of the ultrasonic defoamer was 1500 W) for 45 min to remove the bubbles inside the composite hydrogel, and then placed in a -65°C ultra-low temperature refrigerator for pre-freezing for 7 h. It was then subjected to microwave vacuum freeze-drying (the temperature of the microwave vacuum freeze-drying was -70°C, the microwave power was 2000 W, and the vacuum degree was 12 Pa) for 20 h to obtain a flame-retardant chitosan / carboxyl chitosan / TiO2@MXene composite aerogel with both photocatalytic degradation of dyes.

[0036] The chitosan / carboxyl chitosan / TiO2@MXene composite aerogel prepared in this example has a solubility loss rate of 12.09% and a specific surface area of ​​16.83 m 2 / g, the average pore size is 88.26μm, the porosity is 83.67%, and the limiting oxygen index is 33.2%.

[0037] Through the test of photocatalytic degradation of dye performance, the composite aerogel obtained in this embodiment has a photodegradation rate of 85.96% for methylene blue (MB) dye and a photodegradation rate of 88.37% for rhodamine B (RhB) dye after 2 hours; after 7 cycles of use, the photodegradation rate of the composite aerogel for methylene blue is 64.51% and the photodegradation rate of rhodamine B is 62.85% after 2 hours.

[0038] Example 2 (1) 1.5 g of LiF was dissolved in 30 mL of 9 mol / L HCl solution and stirred at room temperature for 45 min to obtain a mixed solution. Then, 1.5 g of Ti3AlC2 powder was slowly added to the LiF / HCl mixed solution and slowly stirred (60 rpm) at 45 °C for 52 h. The solid was collected by filtration and washed with deionized water four times, then centrifuged at 4500 rpm for 15 min until the pH of the solid was 6.0. The solid was treated with a 580 W high-power ultrasonic machine for 70 min and then centrifuged at high speed (9600 rpm) for 8 min to obtain uniformly dispersed MXene nanosheets.

[0039] (2) Anatase TiO2 sol with a mass concentration of 0.15% was ultrasonically dispersed for 25 minutes, and then MXene nanosheets (the mass ratio of anatase TiO2 to MXene was 2:1) were added and stirred for 18 minutes. Then, 10 mL of anhydrous ethanol was added and ultrasonically treated for 1.5 hours. The mixed solution was transferred to a reactor and subjected to a hydrothermal reaction at 110 °C for 3 hours. After cooling to room temperature, the product was centrifuged and separated, washed with 60% ethanol solution, and then freeze-dried to obtain the TiO2@MXene composite.

[0040] (3) Chitosan was dissolved in 1-ethyl-3-methylimidazolium acetate ionic liquid at pH 4.6 at 70°C to prepare a solution with a mass concentration of 2%, and TiO2@MXene composite (the mass ratio of chitosan to TiO2@MXene composite was 1:1) was added to the solution. Ultrasonic (ultrasonic power was 300 W) chemical reaction was carried out at 60°C for 2 h, and the mixture was allowed to stand for 30 min. Then, low molecular weight carboxyl chitosan (low molecular weight carboxyl chitosan) was added at a mass ratio of chitosan to low molecular weight carboxyl chitosan of 6:1. The carboxyl content at the C6 position is 61.54%, the deacetylation degree is 93.11%, the viscosity-average molecular weight is 5,800, the solubility in water is 22.36 g / 100 mL, and the isoelectric point pH=4.9) and the small molecule cross-linking agent oxalic acid (the mass ratio of chitosan to oxalic acid is 6:1) are cross-linked under microwave radiation (the power of microwave radiation is 720 W, and the microwave radiation temperature is 60°C) for 80 minutes, so that chitosan forms multi-site chemical cross-linking and electrostatic force with low molecular carboxyl chitosan and TiO2@MXene complex.

[0041] (4) After the reaction, the composite hydrogel was aged for 30 min, treated with an ultrasonic defoamer (the power of the ultrasonic defoamer was 1800 W) for 60 min to remove the bubbles inside the composite hydrogel, and then placed in a -70°C ultra-low temperature refrigerator for pre-freezing for 8 h. It was then subjected to microwave vacuum freeze-drying (the temperature of the microwave vacuum freeze-drying was -80°C, the microwave power was 2100 W, and the vacuum degree was 10 Pa) for 20 h to obtain a flame-retardant chitosan / carboxyl chitosan / TiO2@MXene composite aerogel with both photocatalytic degradation of dyes.

[0042] The chitosan / carboxyl chitosan / TiO2@MXene composite aerogel prepared in this example has a solubility loss rate of 10.52% and a specific surface area of ​​21.39 m 2 / g, the average pore size is 80.17μm, the porosity is 86.04%, and the limiting oxygen index is 35.7%.

[0043] Through the test of photocatalytic degradation of dye performance, the composite aerogel obtained in this embodiment has a photodegradation rate of 92.65% for methylene blue (MB) dye and a photodegradation rate of 93.41% for rhodamine B (RhB) dye after 2 hours; after 7 cycles of use, the photodegradation rate of the composite aerogel for methylene blue is 68.55% and the photodegradation rate of rhodamine B is 70.89% after 2 hours.

[0044] Example 3 (1) 2 g of LiF was dissolved in 40 mL of 9 mol / L HCl solution and stirred at room temperature for 50 min to obtain a mixed solution. Then, 2 g of Ti3AlC2 powder was slowly added to the LiF / HCl mixed solution and slowly stirred (speed 82 rpm) at 45 °C for 60 h. The solid was collected by filtration and washed with deionized water 5 times, then centrifuged at 4800 rpm for 18 min until the pH of the solid was 6.2. It was treated with a 620 W high-power ultrasonic machine for 75 min and then centrifuged at high speed (speed 11000 rpm) for 8 min to obtain uniformly dispersed MXene nanosheets.

[0045] (2) Anatase TiO2 sol with a mass concentration of 0.12% was ultrasonically dispersed for 30 min, and MXene nanosheets (the mass ratio of anatase TiO2 to MXene was 3:1) were added and stirred for 18 min. Then, 10 mL of anhydrous ethanol was added and ultrasonically treated for 2 h. The mixed solution was transferred to a reactor and subjected to hydrothermal reaction at 120 °C for 4 h. After cooling to room temperature, the product was centrifuged and separated, washed with 60% ethanol solution, and then freeze-dried to obtain the TiO2@MXene composite.

[0046] (3) Chitosan was dissolved in 1-ethyl-3-methylimidazolium acetate ionic liquid at pH 4.4 at 75°C to prepare a solution with a mass concentration of 3%, and the TiO2@MXene composite (the mass ratio of chitosan to TiO2@MXene composite was 1:1) was added to the solution. The solution was subjected to ultrasonic chemical reaction (ultrasonic power of 300 W) at 60°C for 2 h. The solution was allowed to stand for 35 min. Then, low molecular weight carboxyl chitosan (C of low molecular weight carboxyl chitosan) was added at a mass ratio of chitosan to low molecular weight carboxyl chitosan of 8:1. The 6-position carboxyl content is 70.13%, the deacetylation degree is 95.08%, the viscosity-average molecular weight is 4,200, the solubility in water is 26.31 g / 100 mL, and the isoelectric point pH=4.7) and the small molecule cross-linking agent tartaric acid (the mass ratio of chitosan to tartaric acid is 8:1) are cross-linked under microwave radiation (the power of microwave radiation is 720 W, and the microwave radiation temperature is 60°C) for 120 minutes, so that chitosan forms multi-site chemical cross-linking and electrostatic force with low molecular carboxyl chitosan and TiO2@MXene composite.

[0047] (4) After the reaction, the composite hydrogel was aged for 40 min, treated with an ultrasonic defoamer (the power of the ultrasonic defoamer was 2000 W) for 70 min to remove the bubbles inside the composite hydrogel, and then placed in a -75°C ultra-low temperature refrigerator for pre-freezing for 10 h. It was then subjected to microwave vacuum freeze-drying (the temperature of the microwave vacuum freeze-drying was -84°C, the microwave power was 2200 W, and the vacuum degree was 8 Pa) for 22 h to obtain a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel that was flame retardant and photocatalytically degradable.

[0048] The chitosan / carboxyl chitosan / TiO2@MXene composite aerogel prepared in this example has a solubility loss rate of 7.11% and a specific surface area of ​​32.94 m 2 / g, the average pore size is 60.8μm, the porosity is 90.59%, and the limiting oxygen index is 40.1%.

[0049] Through the test of photocatalytic degradation of dye performance, the composite aerogel obtained in this embodiment has a photodegradation rate of 100% for methylene blue (MB) dye and a photodegradation rate of 98.18% for rhodamine B (RhB) dye after 2 hours; after 7 cycles of use, the photodegradation rate of the composite aerogel for methylene blue is 77.56% and the photodegradation rate of rhodamine B is 73.60% after 2 hours.

[0050] Example 4 (1) 2 g of LiF was dissolved in 40 mL of 9 mol / L HCl solution and stirred at room temperature for 55 min to obtain a mixed solution. Then, 2 g of Ti3AlC2 powder was slowly added to the above LiF / HCl mixed solution and slowly stirred (95 rpm) at 45 °C for 60 h. The solid was collected by filtration and washed with deionized water 5 times, then centrifuged at 4800 rpm for 20 min until the pH of the solid was 6.2. The solid was treated with a 650 W high-power ultrasonic machine for 75 min and then centrifuged at high speed (11800 rpm) for 10 min to obtain uniformly dispersed MXene nanosheets.

[0051] (2) Anatase TiO2 sol with a mass concentration of 0.12% was ultrasonically dispersed for 30 minutes, and MXene nanosheets (the mass ratio of anatase TiO2 to MXene was 4:1) were added and stirred for 18 minutes. Then, 10 mL of anhydrous ethanol was added and ultrasonically treated for 2 hours. The mixed solution was transferred to a reactor and subjected to a hydrothermal reaction at 120 °C for 4.5 hours. After cooling to room temperature, the product was centrifuged and separated, washed with 60% ethanol solution, and then freeze-dried to obtain the TiO2@MXene composite.

[0052] (3) Chitosan was dissolved in 1-ethyl-3-methylimidazolium acetate ionic liquid at pH 4.4 at 75°C to prepare a solution with a mass concentration of 3%, and TiO2@MXene composite (the mass ratio of chitosan to TiO2@MXene composite was 1:1) was added to the solution. Ultrasonic (ultrasonic power was 340 W) chemical reaction was carried out at 65°C for 3 h, and the mixture was allowed to stand for 38 min. Then, low molecular weight carboxyl chitosan (C of low molecular weight carboxyl chitosan) was added at a mass ratio of chitosan to low molecular weight carboxyl chitosan of 9:1. The 6-position carboxyl content is 70.13%, the deacetylation degree is 95.08%, the viscosity-average molecular weight is 4,200, the solubility in water is 26.31 g / 100 mL, and the isoelectric point pH=4.7) and the small molecule cross-linking agent tartaric acid (the mass ratio of chitosan to tartaric acid is 9:1) are cross-linked under microwave radiation (the power of microwave radiation is 760 W, and the microwave radiation temperature is 65°C) for 130 minutes, so that chitosan forms multi-site chemical cross-linking and electrostatic force with low molecular carboxyl chitosan and TiO2@MXene composite.

[0053] (4) After the reaction, the composite hydrogel was aged for 40 min, treated with an ultrasonic defoamer (the power of the ultrasonic defoamer was 2000 W) for 80 min to remove the bubbles inside the composite hydrogel, and then placed in a -78°C ultra-low temperature refrigerator for pre-freezing for 10 h. It was then subjected to microwave vacuum freeze-drying (the temperature of the microwave vacuum freeze-drying was -84°C, the microwave power was 2200 W, and the vacuum degree was 8 Pa) for 22 h to obtain a flame-retardant chitosan / carboxyl chitosan / TiO2@MXene composite aerogel with both photocatalytic degradation of dyes.

[0054] The chitosan / carboxyl chitosan / TiO2@MXene composite aerogel prepared in this example has a solubility loss rate of 9.06% and a specific surface area of ​​30.17 m 2 / g, the average pore size is 66.4μm, the porosity is 89.02%, and the limiting oxygen index is 38.7%.

[0055] Through the test of photocatalytic degradation of dye performance, the composite aerogel obtained in this embodiment has a photodegradation rate of 99.73% for methylene blue (MB) dye and a photodegradation rate of 97.05% for rhodamine B (RhB) dye after 2 hours; after 7 cycles of use, the photodegradation rate of the composite aerogel for methylene blue is 75.02% after 2 hours, and the photodegradation rate of rhodamine B is 72.18%.

[0056] Comparative Example 1 Preparation of chitosan / carboxyl chitosan composite aerogel (without adding TiO2@MXene composite): (1) Chitosan was dissolved in 1-ethyl-3-methylimidazolium acetate ionic liquid at pH 4.4 at 75°C to prepare a solution with a mass concentration of 3%. Then, low molecular weight carboxyl chitosan (the C6 carboxyl content of low molecular weight carboxyl chitosan was 70.13%, the degree of deacetylation was 95.08%, the viscosity-average molecular weight was 0.42 thousand, the solubility in water was 26.31 g / 100 mL, and the isoelectric point pH was 4.7) and small molecular weight crosslinker tartaric acid (the mass ratio of chitosan to tartaric acid was 8:1) were added in a mass ratio of chitosan to low molecular weight carboxyl chitosan of 8:1, and the solution was cross-linked for 120 min under microwave radiation (the microwave radiation power was 720 W and the microwave radiation temperature was 60°C), so that chitosan, low molecular weight carboxyl chitosan and small molecular weight crosslinker tartaric acid formed multi-site chemical crosslinking and electrostatic force.

[0057] (2) After the reaction, the composite hydrogel was aged for 40 min, treated with an ultrasonic defoamer (the power of the ultrasonic defoamer was 2000 W) for 70 min to remove the bubbles inside the composite hydrogel, and then placed in a -75°C ultra-low temperature refrigerator for pre-freezing for 10 h, and then subjected to microwave vacuum freeze-drying (the temperature of microwave vacuum freeze-drying was -84°C, the microwave power was 2200 W, and the vacuum degree was 8 Pa) for 22 h to obtain chitosan / carboxyl chitosan composite aerogel.

[0058] The results show that the dissolution rate of the chitosan / carboxyl chitosan composite aerogel prepared in this comparative example is 16.51%, and the specific surface area is 30.24 m 2 / g, the average pore size is 72.6μm, the porosity is 89.17%, and the limiting oxygen index is 24.5%. The photocatalytic degradation of dyes was tested and the composite aerogel obtained in this comparative example had basically no photodegradation effect on methylene blue (MB) dye and rhodamine B (RhB) dye.

[0059] Comparative Example 2 Preparation of chitosan / carboxyl chitosan / TiO2@MXene composite aerogel (without adding small molecule cross-linking agent): (1) 2 g of LiF was dissolved in 40 mL of 9 mol / L HCl solution and stirred at room temperature for 50 min to obtain a mixed solution. Then 2 g of Ti3AlC2 powder was slowly added to the above LiF / HCl mixed solution and slowly stirred (speed 82 rpm) at 45 °C for 60 h. The solid was collected by filtration and washed with deionized water 5 times, then centrifuged at 4800 rpm for 18 min until the pH of the solid was 6.2. It was treated with a 620 W high-power ultrasonic machine for 75 min and then centrifuged at high speed (speed 11000 rpm) for 8 min to obtain uniformly dispersed MXene nanosheets.

[0060] (2) Anatase TiO2 sol with a mass concentration of 0.12% was ultrasonically dispersed for 30 min, and MXene nanosheets (the mass ratio of anatase TiO2 to MXene was 3:1) were added and stirred for 18 min. Then, 10 mL of anhydrous ethanol was added and ultrasonically treated for 2 h. The mixed solution was transferred to a reactor and subjected to hydrothermal reaction at 120 °C for 4 h. After cooling to room temperature, the product was centrifuged and separated, washed with 60% ethanol solution, and then freeze-dried to obtain the TiO2@MXene composite.

[0061] (3) Chitosan was dissolved in 1-ethyl-3-methylimidazolium acetate ionic liquid at pH 4.4 at 75°C to prepare a solution with a mass concentration of 3%, and TiO2@MXene composite (the mass ratio of chitosan to TiO2@MXene composite was 1:1) was added to the solution. The solution was subjected to ultrasonic chemical reaction (ultrasonic power was 300 W) at 60°C for 2 h. The solution was allowed to stand for 35 min, and then low molecular weight carboxyl chitosan was added at a mass ratio of chitosan to low molecular weight carboxyl chitosan of 8:1. The chitosan (the C6 carboxyl content of low molecular weight carboxyl chitosan is 70.13%, the deacetylation degree is 95.08%, the viscosity average molecular weight is 4,200, the solubility in water is 26.31 g / 100 mL, and the isoelectric point pH=4.7) was cross-linked under microwave radiation (the microwave radiation power was 720 W and the microwave radiation temperature was 60°C) for 120 minutes to form multi-site chemical cross-linking and electrostatic force between chitosan and low molecular weight carboxyl chitosan and TiO2@MXene composite.

[0062] (4) After the reaction, the composite hydrogel was aged for 40 min, treated with an ultrasonic defoamer (the power of the ultrasonic defoamer was 2000 W) for 70 min to remove the bubbles inside the composite hydrogel, and then placed in a -75°C ultra-low temperature refrigerator for pre-freezing for 10 h, and then subjected to microwave vacuum freeze-drying (the temperature of microwave vacuum freeze-drying was -84°C, the microwave power was 2200 W, and the vacuum degree was 8 Pa) for 22 h to obtain chitosan / carboxyl chitosan / TiO2@MXene composite aerogel.

[0063] The results show that the dissolution rate of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel prepared in this comparative example is 20.14% and the specific surface area is 13.36 m 2 / g, the average pore size is 129.4μm, the porosity is 70.46%, and the limiting oxygen index is 30.9%.

[0064] Through the test of photocatalytic degradation of dye performance, the composite aerogel obtained in this comparative example has a photodegradation rate of 88.47% for methylene blue (MB) dye and a photodegradation rate of 87.15% for rhodamine B (RhB) dye after 2 hours; after 7 cycles of use, the photodegradation rate of 51.07% for methylene blue and 48.21% for rhodamine B after 2 hours.

[0065] 2. Testing the samples obtained in the above examples Test Item 1: Test on the dissolution rate, specific surface area, average pore size, porosity and mechanical properties of composite aerogels formed by adding small molecule cross-linking agents of different masses According to the method in Example 3, chitosan / carboxyl chitosan / TiO2@MXene composite aerogels were prepared by changing the mass ratio of chitosan to the small molecule crosslinking agent. The test results of the composite aerogels' dissolution rate, specific surface area, average pore size, porosity, mechanical properties and other indicators are shown in Table 1. The mechanical properties of the composite aerogels were tested by compression on a CMT6104 universal testing machine in accordance with the ASTM D3575-14 standard. The maximum pressure that the composite aerogels can withstand per square meter of area without collapse is a constant compression speed of 2 mm / min.

[0066] Table 1 Test results of physical and chemical properties of composite aerogels

[0067] The invention dissolves chitosan in 1-ethyl-3-methylimidazolium acetate ([EMIM][Ac]) ionic liquid, adds a TiO2@MXene composite material under the action of ultrasound for electrostatic self-assembly, then adds low molecular carboxyl chitosan and a small molecule cross-linking agent under microwave radiation to enhance the cross-linking reaction and electrostatic force, and then obtains a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel with a stable structure, high porosity and a three-dimensional network skeleton through microwave vacuum freeze drying. The data in Table 1 show that by optimizing the amount of small molecule cross-linking agent added, the carboxyl group and anhydride in the small molecule cross-linking agent can be covalently cross-linked with the amino group and hydroxyl group in the chitosan and carboxyl chitosan molecules dissolved in the 1-ethyl-3-methylimidazolium acetate ionic liquid. At the same time, the positively charged amino groups in the chitosan and carboxyl chitosan molecules can also produce hydrogen bonds and electrostatic forces with the -OH, -F, -O and other groups in the TiO2@MXene composite, and further electrostatically self-assemble under the connection of the small molecule cross-linking agent to form a stable three-dimensional skeleton structure, thereby enhancing the mechanical properties of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel. Compared with the composite aerogel samples without adding small molecule cross-linking agents, the composite aerogels with different mass ratios of small molecule cross-linking agents have smaller average pore size and dissolution rate, higher specific surface area and porosity, and significantly improved mechanical properties.

[0068] Test Item 2: Cross-sectional SEM analysis of chitosan / carboxyl chitosan / TiO2@MXene composite aerogel The micropore distribution of the cross section of the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel was observed using a scanning electron microscope (200×). Four composite aerogel samples were taken, the first of which was a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel sample obtained by the method of Comparative Example 2, the second was a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel obtained by the method of Example 1, the third was a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel obtained by the method of Example 2, and the fourth was a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel obtained by the method of Example 3. The test results are shown in Table 1. Figure 3 (a)~(d).

[0069] from Figure 3 It can be seen that the chitosan / carboxyl chitosan / TiO2@MXene composite aerogel presents a typical porous three-dimensional network structure, which indicates that the chitosan amino group dissolved in the 1-ethyl-3-methylimidazole acetate acidic ionic liquid carries a positive charge and can interact with the negatively charged groups such as -OH, -F, and -O on the surface of the TiO2@MXene composite through hydrogen bonds and electrostatic forces. At the same time, the carboxyl groups in the low molecular weight carboxyl chitosan molecules can produce amide bond crosslinks with the amino groups of chitosan, and the amino and hydroxyl groups in the molecules can form multi-site hydrogen bonds with the abundant negatively charged groups on the surface of TiO2@MXene, thereby constructing the skeleton structure of the composite aerogel. The composite aerogel prepared without adding a small molecule crosslinker has a reduced degree of crosslinking between the components of the composite aerogel due to the lack of crosslinking bonds and electrostatic forces generated by the small molecule crosslinker between chitosan, low molecular weight carboxyl chitosan, and TiO2@MXene sheets, and a tight mesh structure cannot be formed, and the aerogel structure stability is relatively loose (see Figure 3 a), and is not conducive to the electrostatic assembly and uniform distribution of TiO2@MXene composite sheets, resulting in a decrease in the photodegradation efficiency and reusability of the composite aerogel. The addition of small molecule crosslinkers can further enhance the covalent bond between chitosan and low molecular weight carboxyl chitosan, as well as the hydrogen bond and electrostatic self-assembly with -OH, -F, -O and other groups on the surface of the TiO2@MXene composite, thereby forming an interconnected and dense three-dimensional porous structure with a smaller pore size and an increased specific surface area (see Figure 3 b~d); At the same time, the TiO2@MXene composite sheets are tightly encapsulated by chitosan and low molecular weight carboxyl chitosan and evenly distributed on the surface of the aerogel. The surface of the composite aerogel becomes rough, which helps to improve the flame retardant and photocatalytic properties of the composite aerogel.

[0070] Test Item 3: Cone calorimetry analysis of chitosan / carboxyl chitosan / TiO2@MXene composite aerogel The fire behavior of the composite aerogel was analyzed using a cone calorimeter. Two composite aerogel samples were taken, the first of which was a chitosan / carboxyl chitosan composite aerogel sample obtained by the method of Comparative Example 1, and the second was a chitosan / carboxyl chitosan / TiO2@MXene composite aerogel obtained by the method of Example 3. The test results are shown in Table 2.

[0071] Table 2 Cone calorimeter test results of composite aerogels

[0072] Ignition time (TTI), peak HRR (PHRR) and total heat release (THR) are several important parameters of the combustion behavior of composite materials during combustion. The chitosan / carboxyl chitosan composite aerogel without adding TiO2@MXene composite reached PHRR at 9s and burned out at 39s. The TTI, PHRR and THR values ​​were 10s, 76.966KW / m 2 and 4.351MJ / m 2 Obviously, chitosan / carboxyl chitosan composite aerogel is an extremely flammable composite material. When chitosan / carboxyl chitosan / TiO2@MXene composite aerogel reaches PHRR at 14s and burns out at 61s, the burning time is 56.4% longer than that of chitosan / carboxyl chitosan composite aerogel without adding TiO2@MXene composite. The TTI, PHRR and THR values ​​are 28s, 39.499KW / m 2 and 3.269MJ / m 2 The PHRR and THR values ​​were 48.67% and 24.86% lower than those of chitosan / carboxyl chitosan composite aerogels, respectively. This indicates that the addition of TiO2@MXene composites can reduce the PHRR and THR during aerogel combustion and prevent the rapid heat release of aerogels. At the same time, Table 2 shows that the total smoke generation (TSP) value of chitosan / carboxyl chitosan / TiO2@MXene composite aerogels is 0.062m 2 , than chitosan / carboxyl chitosan aerogel (0.277m 2 ) is 77.62% lower; at the same time, the addition of TiO2@MXene composite also reduces the release of CO and CO2. This shows that the layered barrier effect of TiO2@MXene composite nanosheets and the synergistic carbonization effect of MXene, chitosan and carboxyl chitosan can enhance the generation of integrated and dense protective carbon layer, thereby inhibiting the emission of smoke during combustion. It can be seen that the addition of TiO2@MXene composite can effectively improve the flame retardant properties of composite aerogel.

[0073] In summary, the present invention dissolves chitosan in 1-ethyl-3-methylimidazolium acetate ([EMIM][Ac]) acidic ionic liquid, adds TiO2@MXene composite material under ultrasonic action for electrostatic self-assembly, then adds low molecular carboxyl chitosan and small molecule cross-linking agent under microwave radiation to enhance cross-linking reaction and electrostatic force, and then prepares chitosan / carboxyl chitosan / TiO2@MXene composite aerogel material with stable structure, good flame retardancy, high photocatalytic activity and three-dimensional network through microwave vacuum freeze drying. The method of the present invention is simple and easy to operate, mild reaction conditions, green and environmentally friendly, and the obtained composite aerogel has the advantages of good mechanical properties, low dissolution rate, high porosity, high flame retardancy, strong photocatalytic activity, etc., and has great application potential in the fields of photodegradation of pollutants, high temperature insulation, flame retardancy and fire prevention.

[0074] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite aerogel having both flame retardancy and photocatalytic degradation of dyes, characterized in that: The composite aerogel is prepared by dissolving chitosan in 1-ethyl-3-methylimidazolium acetate ionic liquid, adding TiO2@MXene complex under ultrasonic action for electrostatic self-assembly, then adding low molecular weight carboxyl chitosan and small molecule cross-linking agent under microwave radiation to enhance cross-linking reaction and electrostatic force, and then performing microwave vacuum freeze-drying to obtain the composite aerogel.

2. The flame-retardant composite aerogel having photocatalytic degradation of dyes according to claim 1, characterized in that: The low molecular weight carboxyl chitosan has a C6 carboxyl content of 50.64-71.26%, a deacetylation degree of 89.17-96.48%, a viscosity average molecular weight of 0.35-0.89 thousand, a solubility in water of 17.83-28.02 g / 100 mL, an isoelectric point pH of 4.7-5.1, and a structural formula as follows: 。 3. The flame-retardant composite aerogel having photocatalytic degradation of dyes according to claim 1, characterized in that: The composite aerogel has a dissolution rate of 7.06-14.51% and a specific surface area of ​​13.72-32.96 m 2 / g, the average pore size is 60.3~96.9μm, the porosity is 81.42~90.68%, and the limiting oxygen index is 30.5~40.1%.

4. A method for preparing the flame-retardant composite aerogel having both photocatalytic degradation of dyes as claimed in any one of claims 1 to 3, characterized in that: The steps include: (1) Dissolve 1-2 g of LiF in 20-40 mL of 9 mol / L HCl solution, stir at room temperature for 30-60 min to obtain a mixed solution, then add 1-2 g of Ti3AlC2 powder, and stir at 45 °C for 48-60 h; collect the solid by filtration and wash it with deionized water for 3-5 times, then centrifuge at 3500-5000 rpm for 10-20 min until the pH of the solid is 6.0-6.4, treat it with a 500-680 W high-power ultrasonic machine for 60-80 min, and then centrifuge it at high speed for 6-10 min to obtain uniformly dispersed MXene nanosheets; (2) ultrasonically dispersing anatase TiO2 sol with a mass concentration of 0.1 to 0.2% for 20 to 30 minutes, adding the MXene nanosheets and stirring and dispersing them for 10 to 20 minutes, then adding 10 mL of anhydrous ethanol and ultrasonically treating them for 1 to 2 hours, transferring the mixed solution to a reactor and performing a hydrothermal reaction at 100 to 120° C. for 3 to 5 hours, cooling to room temperature, centrifuging and separating the product, washing it with an ethanol solution with a mass concentration of 60%, and then freeze-drying it to obtain a TiO2@MXene composite; the mass ratio of anatase TiO2 to MXene nanosheets is 1 to 6:1; (3) Dissolving chitosan in 1-ethyl-3-methylimidazolium acetate ionic liquid at 60-80° C. to prepare a solution with a mass concentration of 1-4%, adding TiO2@MXene composite to carry out ultrasonic chemical reaction at 50-70° C. for 1-3 hours, standing for 20-40 minutes, and then adding low molecular weight carboxyl chitosan and small molecule crosslinking agent to carry out crosslinking reaction under microwave radiation for 45-140 minutes, so that chitosan, low molecular weight carboxyl chitosan and TiO2@MXene composite form multi-site chemical crosslinking and electrostatic force; the mass ratio of chitosan to TiO2@MXene composite is 1:1; the mass ratio of chitosan to low molecular weight carboxyl chitosan is 3-10:1; the mass ratio of chitosan to small molecule crosslinking agent is 4-10:1; the small molecule crosslinking agent is selected from tartaric acid, malic acid, oxalic acid, glutamic acid, maleic acid or maleic anhydride; (4) After the reaction is completed, the composite hydrogel is allowed to stand for 20 to 45 minutes, and is treated with an ultrasonic defoamer for 30 to 90 minutes to remove bubbles inside the composite hydrogel. The composite hydrogel is then placed in an ultra-low temperature refrigerator at -80 to -65°C for pre-freezing for 6 to 10 hours, and then subjected to microwave vacuum freeze drying for 18 to 24 hours to obtain a composite aerogel that is flame retardant and has photocatalytic properties for degrading dyes.

5. The preparation method according to claim 4, characterized in that: In step (3), the pH of the 1-ethyl-3-methylimidazolium acetate ionic liquid is 4.2 to 5.

0.

6. The preparation method according to claim 4, characterized in that: In step (3), the ultrasonic power of the ultrasonic chemical reaction is 240-360 W, the power of the microwave radiation is 620-800 W, and the microwave radiation temperature is 50-65° C.

7. The preparation method according to claim 4, characterized in that: In step (4), the power of the ultrasonic defoamer is 1400-2100W.

8. The preparation method according to claim 4, characterized in that: In step (4), the temperature of the microwave vacuum freeze-drying is -86 to -70°C, the microwave power is 1800 to 2400W, and the vacuum degree is 6 to 15Pa.

9. An application of the flame-retardant composite aerogel having both photocatalytic degradation of dyes according to any one of claims 1 to 3, characterized in that: Used for flame retardancy and / or photocatalytic degradation of dyes in wastewater.

10. The use according to claim 9, characterized in that: The chitosan / carboxyl chitosan / TiO2@MXene composite aerogel after photodegradation of the dye was regenerated by decomposing the dye under ultraviolet irradiation in clean water.

Citation Information

Patent Citations

  • Preparation method of MXene / CS aerogel

    CN116874871A

  • Preparation method of magnetic carboxyl chitosan microsphere and metal organic framework core-shell structure industrial catalyst

    CN117299204A

  • Double-layer MXene-based aerogel composite phase change film as well as preparation method and application thereof

    CN117700828A

  • Chitosan / low-molecular oxidized chitosan / titanium dioxide composite aerogel and application thereof

    CN118059950A

  • Porous polymer nanocomposites with ordered and tunable crystalline and amorphous phase domains

    US20180371190A1

Cited By

  • Flame-retardant high-toughness bio-based composite aerogel as well as preparation method and application thereof

    CN122381418A